Modular design of turning machine tools using ideas software package - Gatalo, Ratko; Rekecki, Jožef; Sakač, Zlatko; Zeljković, Milan; Novaković, Dragoljub; Navalušić, Slobodan (Journal of Production Engineering, 1992)
The paper presents the concept of machine tools’ modular design using the software package I-DEAS. Starting with general remarks and the principles of modular design, the article shows the basic structure of the lathe system developed at the Institute for Production Engineering. Based on this structure, the model of the system for modular design is defined. The model of the system contains four subsystems: 1) recording and checking input data, 2) manipulating the module’s base, 3) machine synthesis, and 4) output definition. After that, the procedure for the creation of the particular module is shown. Since the selection of the first module has a significant impact on the synthesis of the machine, the importance of this step is also emphasized. Machine synthesis continues by adding other modules depending on the required lathe type. The database and module base (3D base) are also shown. In the end, the testing results are presented.